HIGH RISK PERCEPTION OF THE INFECTED SEXUALLY TRANSMITTED INFECTIONS (STI) STI CLINIC ON IN PADANG BULAN PUBLIC HEALTH CENTERS - Ayu Febrini Meutia (JOURNAL OF HEALTHCARE TECHNOLOGY AND MEDICINE, 2015)
Clinical STI (Sexually Transmitted Infections) is a prevention program of the government which aSTI’s to carry out the functions of control and reduce the spread of STIs in sex workers, homosexuals, Transgenders, Customers sex workers, and sexual partner fixed. STI’S showed an increasing prevalence. STI’S is an indicator for the entrance of HIV AIDS. STI prevalence from year to year but the increasing attention to STI’S at this time if neglected.This study is a qualitative study that illustrates the perception of a high risk group for contracting STIs clinic utilization of primary STI’S.Data obtained by using indepth interviews and secondary data obtained from the health center as well as the data - other supporting data. Data processing is done by qualitative descriptive method.The results showedthe informantto obtaininformationaboutSTIsClinicobtained fromfield officerorGovernmental Organization. Their knowledge ofSTIsclinicisonly limitedtothe examinationof HIV/AIDSalone. The wholeinformantsfromthe highriskgroupof contractingSTDsthatsex workersdidnotknow the type-the typeof STIsother thanHIV/AIDS. Perception ofhigh risk of contractingSTIsgroupformedbythe informationthattheycan, they havethe knowledgeandexperiencethey feel.STIclinicsare expected tofurther maximize thedissemination of information onSTIdiseasein detailandaccurately. Expected tosupportcross-sectoral, especially governmentin an effort toincreasethe utilization ofSTIclinic Keywords : Perception , Clinical STI’S , STI’S High-Risk Groups